ANALISIS MISKONSEPSI SISWA PADA MATERI CIRI – CIRI BANGUN DATAR MENGGUNAKAN TES DIAGNOSTIK TWO TIER MULTIPLE CHOICE DI KELAS VB SD NEGERI CIREMAI GIRI - Fattya Rosyada; Ikhsan Karimah, Nurul (Jurnal Profesi Pendidikan, 2025)
This study aimed to identify students' misconceptions regarding the characteristics of flat shapes in mathematics learning, using a two-tier multiple-choice diagnostic test instrument. This research employs a descriptive qualitative approach. The subjects of this study were fifth-grade elementary school students, totaling 25 students. The data used in this study are observation results, two-tier diagnostic test results, diagnostic interviews with students, and documentation. The data analysis method used includes data reduction, data presentation, and conclusion drawing. The validation results indicate that the two-tier diagnostic test instrument meets the criteria for validity and feasibility, achieving an average total score of 43 out of a possible 44, which reflects a positive response; thus, the instrument is highly suitable for use in the field. The results indicated that among grade V elementary school students learning about the characteristics of flat shapes, 29.40% demonstrated complete understanding of the concept, while various types of misconceptions were identified: 10.00% had positive misconceptions (false positives), 7.40% had negative misconceptions (false negatives), 7.80% had pure misconceptions, 12.10% guessed answers, and 15.20% and 17.80% did not understand the concept at all.